Recomposición de la manzana de la Unidad Educativa Bolívar para la creación de un complejo cultural. Ambato- Ecuador - Aguilar Sánchez, Santiago Mateo (2024)
he aim of this paper is to analyses, diagnose, evaluate and integrate a contemporary architec tural language in the central town of Ambato, specifically in the block that includes buildings of patrimonial character as they are the Educational Unit "Bolivar" and the Theater "Lalama". The analysis of the sector allows us to know its historical context, patrimonial importance, and dynamics of the area, as well as its current problems and needs. Thanks to this analysis it has been possible to make an evaluation of each property of the block and with the help of a previous bibliographic and field research have been determined the strategies and criteria of design both architectural and urban that will govern the Total apple composition by creating a cultural complex. This cultural complex integrates contemporary architecture in a heritage context, respecting the main characteristics of the sector and its architectural program is based on educational and cultural activities that existed previously in these facilities. Finally, public space has been integrated into the complex by means of free plants and the inclusion of the recreational areas of the Colegio Bolívar rescuing its historical value. In this way a cultural complex is proposed with the integration of public space and an archi tectural program that supports art and culture in the city.